Indonesian Language Error Analysis In Online Newspaper Media Pangkalpinangpost.com - Lubis, Hakim Prasasti; Hartati, Lasmi (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to analyze the misuse of the Indonesian language in the online newspaper Pangkalpinangpost.com. The focus of the study includes spelling errors, punctuation errors, morphological and syntactic mistakes, as well as ineffective sentence construction. This research employs a descriptive qualitative approach using content analysis. Data were obtained from news articles on the online media portal selected through purposive sampling. The data were analyzed based on the Pedoman Umum Ejaan Bahasa Indonesia (PUEBI). The results show that numerous language errors are still found in the news published by Pangkalpinangpost.com. The most dominant errors include incorrect capitalization, improper use of punctuation, ineffective sentence structures, improper affixation, and syntactically incorrect sentences. The main causes of these errors are time pressure, limited linguistic knowledge of writers, and the absence of final editing before publication. In conclusion, online media must pay more attention to language quality in news writing to serve as a model for proper use of the Indonesian language. Language training for journalists and the involvement of qualified language editors are essential to improve the quality of information.